Maize Resistance to Stem Borers Can Be Modulated by Systemic Maize Responses to Long-Term Stem Tunneling - Rodríguez, Víctor Manuel; Velasco, Pablo; Cao, Ana; Santiago, Rogelio; Malvar, Rosa Ana; Butrón, Ana (Frontiers in Plant Science, 2021)
Scarce attention has been paid to maize (Zea mays L.) resistance induced by corn borer damage, although evidence shows that induced defenses have lower resource allocation costs than constitutive defenses. Maize responses to short- and long-term attacks by the Mediterranean corn borer (MCB, Sesamia nionagrioides) have been previously studied, but the suggested differences between responses could be due to experimental differences. Therefore, in the current study, a direct comparison between short and long-term responses has been made. The objectives were: (i) to determine changes in the level of antibiosis of the stems induced by feeding of Sesamia nonagrioides larvae for two days (short-term feeding) and nine days (long-term feeding), (ii) to characterise the metabolome of the stems’ short- and long-term responses to borer attack and (iii) to look for metabolic pathways that could modulate plant resistance to MCB. Defenses were progressively induced in the resistant inbred and constitutive defenses were broken down in the susceptible inbred. Results suggest that the different resistance of the two inbreds to stem tunneling by MCB could depend on their ability to establish a systemic response. Based on these results, a high throughput look for specific metabolites implicated in systemic induced resistance to maize stem borers is recommended; the current focus on constitutive defense metabolites has not been successful in finding molecules that would be valuable tools for pest control.